Effectiveness and management of Conservation Units in the west and northwest regions of Paraná (Brazil) - Camargo, Mariele P.; Aranha, José Marcelo R.; Menezes, Márcia S. (Acta Biológica Paranaense, 2018)
The implementation of conservation units is an important strategy to conserve biodiversity, however, their consolidation as an effective mechanism for protecting natural resources faces several challenges. Therefore, the objective of this work was to evaluate the effectiveness and management of nine conservation units in the west and northwest regions of the state of Paraná, Brazil, by application of questionnaires, and interviews with managers in these areas. All evaluated conservation units had insufficient number of employees to meet their demand, and the management plan of 56% of the 89% units that had a management plan were outdated. According to the adopted criteria to evaluate the effectiveness of these conservation units, 67% of them presented satisfactory implementation effectiveness, and management conditions, because they have minimally fulfilled their objectives, despite the several economic, political and social barriers.